2017
DOI: 10.1163/15692108-12341099
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of The United States-Pakistan Relationsin American Newspapers

Abstract: The relations between the United States of America and Pakistan have a significant impact on the world’s politics as well as in shaping the future of the globe. However, the relations between the two countries have been passing through a lot of ups and downs during the last seven decades. Media have a pivotal role in framing and shaping this ‘love and hate’ relationship. The purpose of this study was to investigate the coverage of the United States-Pakistan relations by the American newspapers because the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…According to Riaz (2017), American newspapers portrayed a highly negative image of Pakistan and most of the coverage about the bilateral relations was found as negative. Wu and Coleman (2009) found that attribute agenda setting affect extensively on the audience than prominence of issues.…”
Section: Introductionmentioning
confidence: 99%
“…According to Riaz (2017), American newspapers portrayed a highly negative image of Pakistan and most of the coverage about the bilateral relations was found as negative. Wu and Coleman (2009) found that attribute agenda setting affect extensively on the audience than prominence of issues.…”
Section: Introductionmentioning
confidence: 99%